2006
DOI: 10.1143/jjap.45.l497
|View full text |Cite
|
Sign up to set email alerts
|

Structure Analysis of ZrB2(0001) Surface Prepared by ex situ HF Treatment

Abstract: The surface structure of ZrB 2 (0001) was investigated using coaxial impact-collision ion scattering spectroscopy (CAICISS). The ZrB 2 (0001) 1 Â 1 surface was prepared by HF solution treatment and annealing in vacuum. It was directly evidenced that the ZrB 2 (0001) surface is terminated with a Zr layer. Moreover, we found that the interlayer spacing between the first Zr layer and the second B layer is expanded by 20% with regard to c-axis lattice constant. Since small amount of O atoms were detected after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Experimental studies by means of coaxial impact-collision ion scattering spectroscopy 32 and surface phonon-dispersion data measured by HREELS 33 corroborate that the ZrB 2 (0001) surface is terminated with a Zr layer. This conclusion is supported by several DFT studies 34,35 that show that the Zrterminated surface is more stable than the B-terminated over a wide range of allowed chemical potentials.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Experimental studies by means of coaxial impact-collision ion scattering spectroscopy 32 and surface phonon-dispersion data measured by HREELS 33 corroborate that the ZrB 2 (0001) surface is terminated with a Zr layer. This conclusion is supported by several DFT studies 34,35 that show that the Zrterminated surface is more stable than the B-terminated over a wide range of allowed chemical potentials.…”
Section: Resultsmentioning
confidence: 76%
“…We have carried out a complete minimization of both the force acting over each atom and the stress tensor allowing volume and shape relaxation in order to obtain the equilibrium lattice parameters. Table I Experimental studies by means of coaxial impact-collision ion scattering spectroscopy 32 and surface phonon-dispersion data measured by HREELS 33 corroborate that the ZrB 2 (0001) surface is terminated with a Zr layer. This conclusion is supported by several DFT studies 34,35 that show that the Zr-terminated surface is more stable than the B-terminated over a wide range of allowed chemical potentials.…”
Section: Bulk and Slab Calculationsmentioning
confidence: 70%
“…They also simulated the structural configuration of silicene on the ZrB 2 (0001) surface . By using coaxial impact‐collision ion scattering spectroscopy, Katayama et al found that the ZrB 2 (0001) surface prepared by HF treatment was Zr‐terminated, but the outmost layer distance was expanded by 20% over c‐axis lattice constant, which was supposed to be resulted from residual O atoms . After analyzing the surface phonon dispersion, Aizawa et al revealed that ZrB 2 (0001) surface was terminated by Zr layer, and with the adsorption of excess boron, an ordered structure of 3×3 (R ± 30°) appeared at the B coverage of about 0.8 monolayer .…”
Section: Introductionmentioning
confidence: 99%
“…8 By using coaxial impact-collision ion scattering spectroscopy, Katayama et al found that the ZrB 2 (0001) surface prepared by HF treatment was Zr-terminated, but the outmost layer distance was expanded by 20% over c-axis lattice constant, which was supposed to be resulted from residual O atoms. 9 After analyzing the surface phonon dispersion, Aizawa et al revealed that ZrB 2 (0001) surface was terminated by Zr layer, 10 and with the adsorption of excess boron, an ordered structure of ffiffi ffi 3 p  ffiffi ffi 3 p (R AE 30°) appeared at the B coverage of about 0.8 monolayer. 11 They also investigated the stability of ZrB 2 (0001) surfaces using first-principles calculations and molecular-dynamic simulations, 12,13 and good agreement with the experimental results was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The clean (0001) surface is terminated with a Zr layer [6]. The oxidization of ZrB 2 has been studied for a powder ZrB 2 [7,8] and a single crystal as a substrate for GaN epitaxial formation [9,10], as well as for a basic study of surface oxidation [11,12]. Recently, the oxidization of ZrB 2 nanoparticle has been reported by G. Zhao, et al in 2014 [13].…”
Section: Introductionmentioning
confidence: 99%